Edukasi Bahaya Asap Rokok untuk Pembentukan Generasi Sehat di SMP Negeri 14 Banda Aceh - Hasanah, Mauizah; Rosma, Fatemah; Fajriana, Nurul; Hanum, Ulia; Aini, Qurratu; Suwarniati, Suwarniati; Rizki, Cut Novrita; Zahara, Meutia (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2026)
Smoking behavior among adolescents is a health problem that may cause long-term impacts on both active and passive smokers. This community service activity aimed to improve students’ understanding and awareness of the dangers of cigarette smoke through an educational approach combined with a simple demonstration. The activity was conducted at SMP Negeri 14 Banda Aceh involving seventh and eighth grade students. The methods included interactive lectures on harmful chemical substances in cigarettes and their effects on the respiratory system, as well as a lung model demonstration to visualize the process of smoke inhalation and the accumulation of hazardous residues. The results showed that students’ knowledge of the dangers of smoking increased, they were able to identify harmful chemical components in cigarettes, and they demonstrated more critical attitudes toward smoking behavior and exposure to secondhand smoke. The visual demonstration helped students understand the concepts more concretely and fostered early preventive awareness. It can be concluded that this activity was effective as an experience-based health education model to support the development of a young generation who are aware of the importance of living free from cigarette smoke.